Control interno operativo y su incidencia en el manejo económico financiero de la empresa importadora menfri año 2017-2018. - Vivas Urdánigo, Narcisa (2020)
The purpose of this research project is to evaluate the incidence of internal operational control in the economic and financial management of the Importadora MENFRI company from 2017 to 2018. The theoretical framework was made based on the conceptual, theoretical and legal foundation of the research carried out. The inductive, deductive, historical-logical and descriptive methods were applied, a diagnosis of the current situation was made and subsequently internal control levels were measured through the application of the form, financial and activity indicators were applied. As a result of the investigation, it was possible to determine that the level of internal operational control in transactional processes corresponds to a moderate level, it was also shown that when applying the liquidity and solvency ratios there is a weak interpretation for financial decision-making, they were also evaluated the operation in the procedures for recovering accounts receivable, reflecting that the credit policies are not complied with, also determined that 40% of accounts receivable belong to past due loans.